2022
DOI: 10.1002/lio2.821
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of sinonasal inverted papilloma: An update

Abstract: Objective Sinonasal inverted papilloma (IP) and its clinical features have been widely studied, but there are few studies delving into its etiology and risk factors. A narrative review was conducted to summarize a contemporary understanding of the potential etiologies of IP, including immunologic/inflammatory, viral, genetic, and environmental causes. Study Design Review. Methods A MEDLINE search was conducted through August 11, 2021, focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
8
0
1
Order By: Relevance
“…3 While its etiology remains undefined, several studies have found a correlation between SNIP and chronic inflammation. 8,9 Furthermore, one study also found an association between occupational exposure and SNIP. 8 However, larger-scale studies are needed to confirm the significance of these findings.…”
Section: Discussionmentioning
confidence: 96%
“…3 While its etiology remains undefined, several studies have found a correlation between SNIP and chronic inflammation. 8,9 Furthermore, one study also found an association between occupational exposure and SNIP. 8 However, larger-scale studies are needed to confirm the significance of these findings.…”
Section: Discussionmentioning
confidence: 96%
“…Inverted papilloma (IP) is an unusual type of benign tumor, accounting for 0.5-4% of nasosinus tumors, 99% of which are unilateral [1][2][3]. It progresses slowly, marked by recurrence, bone lysis and transformation to malignancy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF and epidermal growth factor receptor (EGFR) (exon 20 mutations) have also both been implicated in the development of SNIP [12]. Additional data have shown the upregulation of speci c genes in SNIP samples with carcinoma or carcinoma-in-situ when compared to SNIP without dysplasia [11].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study suggested the potential role of chronic in ammation [6,7] and viral (human papillomavirus and Epstein-Barr virus) infection in the etiology of SNIP [8][9][10]. At the molecular level, several cell cycle and angiogenic factors, such as Ki67, vascular endothelial growth factor (VEGF), and Akt/mTOR have been implicated in the development and progression of SNIP [11]. VEGF and epidermal growth factor receptor (EGFR) (exon 20 mutations) have also both been implicated in the development of SNIP [12].…”
Section: Introductionmentioning
confidence: 99%